2014
DOI: 10.1186/1475-2875-13-181
|View full text |Cite
|
Sign up to set email alerts
|

The challenge to avoid anti-malarial medicine stock-outs in an era of funding partners: the case of Tanzania

Abstract: BackgroundBetween 2007 and 2013, the Tanzanian public sector received 93.1 million doses of first-line anti-malarial artemisinin-based combination therapy (ACT) in the form of artemether-lumefantrine entirely supplied by funding partners. The introduction of a health facility ACT stock monitoring system using SMS technology by the National Malaria Control Programme in mid 2011 revealed a high frequency of stock-outs of ACT in primary care public health facilities. The objective of this study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Being engaged in gay community was also strongly associated with being retained in care among MSM living with HIV 12 months or more. These findings highlight the importance of a comprehensive approach to HIV for MSM, one that views communityled and risk reduction programs as critically integral to successful and sustained service provision along the HIV care continuum [32,33].…”
Section: Notes: or = Odds Ratio CI = Confidence Intervalmentioning
confidence: 99%
“…Being engaged in gay community was also strongly associated with being retained in care among MSM living with HIV 12 months or more. These findings highlight the importance of a comprehensive approach to HIV for MSM, one that views communityled and risk reduction programs as critically integral to successful and sustained service provision along the HIV care continuum [32,33].…”
Section: Notes: or = Odds Ratio CI = Confidence Intervalmentioning
confidence: 99%
“…At the end of the pilot period, stock-outs of AL were eliminated and RDT stock-outs declined by 24 percentage-points. The platform has since been scaled up in Tanzania to include over 5,000 public health facilities across the country [83,84].…”
Section: Mhealth Solutionsmentioning
confidence: 99%
“…Reminders were sent automatically to the health worker's phone. If the health worker responded within 27 hours, they received credit on their phone (TZs 1,000, equivalent to USD 0.70) for personal use (pay for performance) (10). These SMS were free of charge thanks to an agreement with the mobile service provider.…”
Section: Introductionmentioning
confidence: 99%
“…SMS for Life has been described in the literature before (9,10). Barrington et al(9) presented the successful pilot results and Mikkelsen-Lopez et al (10) showed that after two years of scale-up, health facilities continued to experience severe antimalarial stock-outs. Both papers studied the programme using a quantitative approach and did not explore the reasons behind the results.…”
Section: Introductionmentioning
confidence: 99%